Effects of Hexane Root Extract of Ferula hermonis Boiss. on Human Breast and Colon Cancer Cells: An In Vitro and In Vivo Study - Nael Abutaha (BioMed Research International, 2019)
Breast and colon cancers are leading causes of cancer-related deaths globally. Plants are a potential source of natural products that may be used for the treatment of cancer. Ferula hermonis (FH) is reported to have diverse therapeutic effects. However, there are few reports on the in vitro anticancer potential of FH extract. Our results showed that the Ferula hermonis root hexane extract (FHRH) can induce dose-dependent cytotoxic effects in breast and colon cancer cells with MTT IC50 values of 18.2 and 25 μg/ml, respectively. The FHRH extract induced apoptosis in both breast and colon cancer cells; this was confirmed by light and nuclear staining, q-PCR, and caspase 3/7 activation. This study also demonstrated the antitumor activity of FHRH in 9,10-dimethylbenz[α]anthracene DMBA-induced rodent mammary tumor model. The GC/MS analysis revealed the presence of 3,5-Dimethylbenzenemethanol, Alpha-Bisabolol, Alpha-pinene, Beta-pinene, and Baccatin III that have various pharmacological potentials. Overall, the present study suggests that FHRH extract possesses anticancer potential which is mediated through apoptotic effects in MDA-MB-231 and LoVo cells. The present study also considered a basis for further investigations into the potential use of FHRH extract as an anticancer therapy for breast and colon cancers.